ETYMOLOGICAL DESCRIPTION OF LITERATURE TERMS IN THE EXPLANATORY DICTIONARIES OF THE UZBEK LANGUAGE - Khudoyberdiyeva Makhbuba Murodovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article talks about the research work carried out in the field of terminology of linguistics, the lexicographic features of the terms related to the field of Uzbek linguistics, the etymological description of the terms of literary studies in the explanatory dictionaries in the Uzbek language. The purpose of the etymological description of the existing terms in the language is to determine when, from which language a certain word was borrowed, according to the form of its formation, in what form and meaning it appeared on the basis of which language material. In this regard, a number of studies conducted in linguistics show that it is important to study the etymological classification of terms in field terminology.